Impact of benefits, work culture and career development on employee engagement and organizational commitment - Ranjan, Rajesh; Arora, Saurabh; Srivastava, D.K (International Journal of Innovative Research and Scientific Studies, 2025)
Many of the Business leaders and professionals are unaware or have a very limited information about the factors affecting job satisfaction and how it is related to employee engagement and work or organizational commitment. Today Employee engagement has become one of the biggest challenges for the companies as the engagement between the employees is on decline and it becomes a critical issue for the organizations or firms recovering from recession trauma. Today the role of employee engagement has become very important for the company as if the employee is not engaged, satisfied, and committed then there may be case of talent mobility. The purpose of the study is to investigate the impact of benefits, work culture and career development on employee engagement and work or organizational commitment. The main aim is to create awareness in employees about Career Satisfaction and Employee Engagement by analyzing that how it is positively related to Organization Commitment. Hypothesis was developed and tested on a sample size. A valid and reliable Questionnaire was used as data collection tool.